How fullerene derivatives (FDs) act on therapeutically important targets associated with diabetic diseases - ERDEM, SAFİYE (My University, 2022)
Fullerene derivatives (FDs) belong to a relatively new family of nano-sized organic compounds. They are widely applied in materials science, pharmaceutical industry, and (bio) medicine. This research focused on the study of FDs in terms of their potential inhibitory effect on therapeutic targets associated with diabetic disease, as well as analysis of protein-ligand binding in order to identify the key binding characteristics of FDs. Therapeutic drug compounds when entering the biological system usually inevitably encounter and interact with a vast variety of biomolecules that are responsible for many different functions in organisms. Protein biomolecules are the most important functional components and used in this study as target structures. The structures of proteins [(PDB ID: 1BMQ, 1FM6, 1GPB, 1H5U, 1US0)] belonging to the class of anti-diabetes targets were obtained from the Protein Data Bank (PDB). Protein binding activity data (binding scores) were calculated for the dataset of 169 FDs related to these five proteins. Subsequently, the resulting data were analyzed using various machine learning and cheminformatics methods, including artificial neural network algorithms for variable selection and property prediction. The Quantitative Structure-Activity Relationship (QSAR) models for prediction of binding scores activity were built up according to five Organization for Economic Co-operation and Development (OECD) principles. All the data obtained can provide important information for further potential use of FDs with different functional groups as promising medical antidiabetic agents. Binding scores activity can be used for ranking of FDs in terms of their inhibitory activity (pharmacological properties) and potential toxicity. (c) 2022 The Authors. Published by Elsevier B.V. on behalf of Research Network of Computational and Structural Biotechnology. This is an open access article under the CC BY license (http://creativecommons. org/licenses/by/4.0/).
Keywords: Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Applied Microbiology and Biotechnology; Molecular Medicine; Biochemistry; Structural Biology; Fullerene-based nanoparticles; Fullerene derivatives; Neural network models; Anti-diabetic targets; Protein-ligand binding; QSAR; NANOPARTICLES; ANTIOXIDANTS; INHIBITION; VALIDATION; MANAGEMENT; CHEMISTRY; TOXICITY; RECEPTOR; DOCKING; Fullerene-based nanoparticles; Fullerene derivatives; Neural network models; Anti-diabetic targets; Protein–ligand binding